SANAD-BASED DAKWAH METHOD: A STUDY OF THE TEACHING TRADITION AND EXAMPLE OF K.H. MUHAMMAD ARWANI AMIN SA'ID KUDUS - Imam Fatkhullah; Yuzril Mahendra; Muhammad Firdaus (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study is motivated by the decline of moral and spiritual authority in modern Islamic da’wah, which tends to be pragmatic and rhetorical. The research aims to analyze the sanad-based da’wah method practiced by K.H. Muhammad Arwani Amin Sa’id at Yanbu‘ul Qur’an Islamic Boarding School in Kudus as a model emphasizing the continuity between knowledge (‘ilm), ethics (adab), and practice (‘amal). Using a qualitative approach through library research, this study examines Arwani’s works, biography, and teaching tradition. The findings reveal that sanad in Arwani’s da’wah functions as a system of value transmission integrating intellectual, moral, and spiritual dimensions through talaqqi (direct learning), mushafahah (face-to-face transmission), and exemplary conduct (uswah hasanah). This approach unites sanad al-‘ilm, sanad al-adab, and sanad al-amal, resulting in an authentic and transformative da’wah bil hal (preaching through action). This study concludes that sanad da'wah is a relevant paradigm for contemporary Islamic da'wah which is rooted in tradition but oriented towards character formation. Its implication suggests that this model can be recontextualized in education and digital da’wah to strengthen scholarly authority, ethical integrity, and moderate Islamic leadership in the modern era.